2009
DOI: 10.1161/strokeaha.109.558049
|View full text |Cite|
|
Sign up to set email alerts
|

Brain Microbleeds Relate to Higher Ambulatory Blood Pressure Levels in First-Ever Lacunar Stroke Patients

Abstract: Background and Purpose— Hypertension is an important risk factor for brain microbleeds (BMBs) in lacunar stroke patients. However, beyond the qualitative label “hypertension,” little is known about the association with ambulatory blood pressure (BP) levels. Methods— In 123 first-ever lacunar stroke patients we performed 24-hour ambulatory BP monitoring after the acute stroke-phase. We counted BMBs on T2*-weighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 25 publications
1
60
1
2
Order By: Relevance
“…Our results are concordant with previous research by Staals et al, 33 where 8.9% of patients had only lobar CMBs, 13.8% had only deep CMBs, and 5.7% had combined (both deep and lobar) CMBs. In our population, we did not find any CMBs in the brain stem.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are concordant with previous research by Staals et al, 33 where 8.9% of patients had only lobar CMBs, 13.8% had only deep CMBs, and 5.7% had combined (both deep and lobar) CMBs. In our population, we did not find any CMBs in the brain stem.…”
Section: Discussionsupporting
confidence: 93%
“…Symmetric hypointensities in the globi pallidi, likely to represent calcification, and sulcal flow voids from cortical vessels were disregarded. 33 Microbleeds were classified in each cerebral hemisphere (and for infratentorial lesions, these were considered in the right/left cerebellum of right/left side of the brain stem) as absent (grade 1), mild (grade 2; total number of microbleeds, 1-2), moderate (grade 3; total number of microbleeds, 3-10), and severe (grade 4; total number of microbleeds, Ͼ10), according to Lee and colleagues. 34 …”
Section: Cmbs Definition and Ratingmentioning
confidence: 99%
“…12 Briefly, we prospectively recruited patients with a first-ever lacunar stroke at Maastricht University Medical Center from May 2003 to January 2008 and at Orbis Medical Center Sittard, The Netherlands from September 2004 to April 2007. Lacunar stroke was defined as an acute lacunar stroke syndrome with a small, deep infarct on MRI compatible with the clinical findings, or, if MRI did not show a compatible lacunar lesion, one of the established clinical lacunar stroke syndromes.…”
Section: Patient Recruitmentmentioning
confidence: 99%
“…2,10 Previous studies showed that elevated BP levels are associated with each of the MRI markers of cSVD separately. [11][12][13][14] However, these studies did not provide an overall measure for the total burden of cSVD. Because these markers may occur simultaneously in a patient and are all considered to be caused by cSVD, it seems rather artificial to investigate the presence of only 1 MRI marker while disregarding the others.…”
mentioning
confidence: 99%
“…Brain microbleeds (BMB) are associated with ischemic and hemorrhagic stroke, cerebral amyloid angiopathy, neurotrauma, Alzheimer's disease, vascular dementia, cognitive decline, hypertension, and aging (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The presence of BMB in ischemic stroke, intracerebral hemorrhage, and cerebral amyloid angiopathy is associated with future hemorrhage (2,(17)(18)(19).…”
mentioning
confidence: 99%